Genetic diversity estimates in landraces of pumpkin (Cucurbita moschata) from North Eastern Himalayan region of India using agro-morphological and molecular traits - BARMAN, ARINDAM; ANSHUMALI, ANSHUMALI (The Indian Journal of Agricultural Sciences, 2018)
The present investigation was carried out to assess the diversity existing among the landraces of pumpkin (Cucurbita moschata Duch.) from North Eastern Himalayan region of India. Clustering analysis based on morphological and molecular traits exhibited high level of genetic diversity and grouped the pumpkin landraces into 5 major clusters. Maximum and minimum inter-cluster average D2 values obtained were 442.27 and 86.29, respectively. High degree of correlation was found between diversity obtained by morphological and molecular traits. The highest and lowest PIC values of SSR markers observed was 0.91 (OCM2) and 0.30 (OCM9) respectively and the Jaccard’s similarity coefficient ranged from 0.51 to 0.92. The most divergent landraces obtained (GHP 1, GHP 26, GHP 43, GHP 51, GHP 52 GHP 56) from this study can be effectively utilized in future pumpkin breeding programme for development of new hybrid combinations.